Audit and Assurance Practices to Emerging Global Regulatory Landscapes - Susanto, Edy; Kalsum, Ummu (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
The study explores contemporary audit and assurance practices within emerging global regulatory frameworks, aiming to elucidate their evolution, challenges, and implications. The purpose is to analyze the impact of international accounting and auditing standards adoption, particularly IFRS and ISAs, on audit practices and regulatory landscapes. Employing a systematic literature review methodology, the research synthesizes existing scholarly works to uncover patterns and trends in audit practices. Findings indicate a significant shift towards convergence in audit practices across jurisdictions due to globalization and regulatory harmonization efforts. However, challenges persist, including variations in interpretation and application of standards, as well as the need for auditors to adapt to emerging risks and technologies. The discussion highlights the role of risk-based auditing methodologies in addressing contemporary business complexities and stakeholder expectations. Implications suggest the necessity for continuous adaptation and innovation in audit practices, leveraging technology, collaboration among stakeholders, and regulatory oversight to ensure audit quality and relevance.